Accuracy of intraocular lens calculations in eyes with keratoconus. Issue 3 (28th March 2023) - Vandevenne, Magali M.S.; Webers, Valentijn S.C.; Segers, Maartje H.M.; Berendschot, Tos T.J.M.; Zadok, David; Dickman, Mor M.; Nuijts, Rudy M.M.A.; Abulafia, Adi
Abstract : Recently, 2 keratoconus-adjusted formulas, Kane keratoconus and Barrett True-K for keratoconus, were introduced to calculate IOL power in patients with keratoconus. These formulas improve the prediction accuracy in patients with keratoconus. Abstract : Purpose: To compare the prediction accuracy of the Barrett True-K for keratoconus with standard formulas (SRK/T, Barrett Universal II, and Kane) and the Kane keratoconus formula. Setting: Shaare Zedek Medical Center, Jerusalem, Israel, and University Eye Clinic, Maastricht, the Netherlands. Design: Multicenter retrospective case series. Methods: Eyes with stable keratoconus undergoing cataract surgery were included. The predicted refractions were calculated for SRK/T, Barrett Universal II, Barrett True-K for keratoconus (predicted and measured), Kane, and Kane adjusted for keratoconus formulas. Primary outcomes were prediction error (PE), absolute error (AE), and percentage of eyes with PE ±0.25 diopters (D), ±0.50 D, and ±1.00 D. Subgroup analyses were performed based on the severity of the keratoconus. Results: 57 eyes were included in the study. The PE was not significantly different from zero for SRK/T, Barrett True-K (predicted and measured), and Kane keratoconus formulas (range 0.09 to 0.22 D, P > .05). The AE of Barrett True-K predicted (median 0.14 D) and Barrett True-K measured (median 0.10 D) were significantly lower from Barrett Universal II (median 0.47 D) and Kane (median 0.50 D), P < .001. Conclusions: The Barrett True-K formulas for keratoconus had higher prediction accuracy as compared with new generation formulas and a similar prediction accuracy as compared with the Kane keratoconus formula.